Education, Press and Hinterland ff Northern Minas Gerais: place(s) of stories - Mello, Rita; Reis, Filomena; Reis, João; Almeida, Shirley (Educação, Escola & Sociedade, 2017)
This work aimed to investigate the local historiography, in the sense of thinking about education, especially in the northern region of Minas Gerais, whose focus in Montes Claros focused since the 1940 to 1980, situated in the field of adult and youth education. The methodology was in the press through the analysis of the Newspaper Gazeta do Norte and the North, as well as official documents and memorialistas. The results show how the trajectories of education were built, marked by political and pedagogical halting at a time when the Northern sertão of Minas Gerais was considered a "habitual resistance to illiteracy", as "rude and undisciplined ", helpless and excluded from the benefits, or why not say, abandoned to their fate in relation to several aspects and, especially in relation to the EJA. Keywords: History. Press. EJA. North of Minas Gerais. Montes Claros.